Neuronal ICAM-5 Plays a Neuroprotective Role in Progressive Neurodegeneration - Birkner, Katharina; Loos, Julia; Gollan, René; Steffen, Falk; Wasser, Beatrice; Ruck, Tobias; Meuth, Sven G.; Zipp, Frauke; Bittner, Stefan (Frontiers in Neurology, 2019)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS) leading to CNS inflammation and neurodegeneration. Current anti-inflammatory drugs have only limited efficacy on progressive neurodegenerative processes underlining the need to understand immune-mediated neuronal injury. Cell adhesion molecules play an important role for immune cell migration over the blood-brain barrier whereas their role in mediating potentially harmful contacts between invading immune cells and neurons is incompletely understood. Here, we assess the role of the CNS-specific neuronal adhesion molecule ICAM-5 using experimental autoimmune encephalomyelitis (EAE), an animal model of MS. ICAM-5 knockout mice show a more severe EAE disease course in the chronic phase indicating a neuroprotective function of ICAM-5 in progressive neurodegeneration. In agreement with the predominant CNS-specific function of ICAM-5, lymphocyte function-associated antigen 1 (LFA-1)/ICAM-1 contact between antigen-presenting cells and T helper (Th)17 cells in EAE is not affected by ICAM-5. Strikingly, intrathecal application of the shed soluble form, sICAM-5, ameliorates EAE disease symptoms and thus might serve locally as an endogenous neuronal defense mechanism which is activated upon neuroinflammation in the CNS. In humans, cerebrospinal fluid from patients suffering from progressive forms of MS shows decreased sICAM-5 levels, suggesting a lack of this endogenous protective pathway in these patient groups. Overall, our study points toward a novel role of ICAM-5 in CNS autoinflammation in progressive EAE/MS.